Implementasi KUHAP Dalam Pelaksanaan Upaya Paksa Terhadap Tersangka Kasus Korupsi Pada Proyek SPAM Buntu Burake Oleh Kejaksaan Negeri Tana Toraja - Nellan Masirri; Ahmad Aswar Rowa; Budi Arta Pradana Nongtji (Journal Law and Government, 2026)
This study aims to examine the application of the Criminal Procedure Code (KUHAP) regarding the use of coercive measures against the suspect in the Buntu Burake Drinking Water Supply System (SPAM) corruption case by the Tana Toraja District Attorney's Office, and to analyze the legal basis for these measures. This is an empirical legal study employing a socio-legal (juridical-empirical) approach, conducted at the Tana Toraja District Attorney's Office. Data were collected through interviews, observation, documentation, and literature review, and subsequently analyzed qualitatively. The results indicate that the application of the KUHAP regarding coercive measures against the suspect in the Buntu Burake SPAM corruption case was carried out through investigative stages involving the collection of project documents, witness examinations, the gathering of evidence, the formal naming of the suspect, and the seizure of documents and evidence related to the case. The naming of the suspect was based on at least two pieces of valid evidence, in accordance with Article 184 of the KUHAP and Constitutional Court Decision Number 21/PUU-XII/2014. The legal basis for implementing these coercive measures refers to Article 1 point 2, Article 1 point 14, Article 38, and Article 184 of the KUHAP, as well as Article 30 paragraph (1) letter d of Law Number 11 of 2021 concerning the Prosecution Service of the Republic of Indonesia. Thus, the application of the KUHAP regarding coercive measures against the suspect in the Buntu Burake SPAM corruption case by the Tana Toraja District Attorney's Office has been carried out in accordance with applicable criminal procedural law provisions.